Inequalities and participation in the digital society: online experiences among children and adolescents in Brazil and Chile - Daniela Trucco; Patricio Cabello; Magdalena Claro (CEPAL Review, 2022)
This paper presents a comparative analysis of the Global Kids Online research network data from Brazil and Chile in 2016 relating to children’s digital access, uses and skills. Results show that high-frequency users tend to be from higher socioeconomic groups. Girls and higher-income children perceive higher levels of risk on the Internet. The most common areas of use are related to learning and social life. The type of guidance that children receive matters: active mediation strategies at home and school are vital for increasing children’s digital opportunities, while restrictive mediation tends to reduce them. Also, parental mediation appears to be unequally distributed, showing differences by age, gender and socioeconomic group. These results contribute to discussions on promoting digital opportunities and reducing risks.